Uptake of hepatitis B vaccination and associated factors among health sciences students, Mogadishu, Somalia - Hassan, Yahye Sheikh Abdulle; Hassan, Shafie Abdulkadir; Ahmed, Nur Rashiid (Frontiers in Public Health, 2023)
Hepatitis B is a potentially fatal liver infection caused by the hepatitis B virus (HBV). It is a serious issue for global health. It considerably raises the risk of cirrhosis and liver cancer-related death and can result in chronic infection. The risk of infection is high among health sciences students due to the risk of occupational contact with fluids from infected patients and the risk of needle stick injury. There is no data available about HBV vaccination uptake among Health Sciences students in Somalia. Therefore, this study aimed to determine HBV vaccination uptake and associated factors towards HBV among health science students in Somalia. A cross-sectional study was undertaken among health sciences students from August to October 2022. Data were gathered using Kobo Toolbox using a standardised questionnaire with questions on characteristics, knowledge attitude, and HBV prevention practices. A total of 569 students were involved in the study. Stata version 15 was utilised for the analysis. Bivariate and multivariate logistic regression analysis, as well as descriptive statistics, were performed. In order to assess the existence and significance of the relationship between the outcome and risk factors, an adjusted odds ratio with a 95% confidence interval (CI) was used. Statistical significance was considered as a P-value ≤ 0.05.Of the 569 study participants, 33.4% (95%CI: 29.6-37.4) received a full dose of the HBV vaccine in this study. Participants had good HBV prevention knowledge, attitudes, and practices at 69.6%, 37.96%, and 50.6%, respectively. The lack of access and the high cost of the vaccine were the reasons for not taking the vaccine. Second-year (AOR: 0.22(0.12-0.43)). Positive attitude (AOR: 0.54(0.31-0.93)), and good practice ))The study indicated that few 33.4% of health sciences students had received the required HBV vaccination doses, academic year, attitude, and practice were significantly associated with full-dose vaccination status. The unavailability of the vaccine and the high cost of vaccination were the most common reasons for not taking the vaccine. It is recommended that students receive vaccinations before beginning clinical rotations, and give instruction on infection prevention strategies and general precautions, particularly regarding HBV infection.